A STUDY ON THE TEACHER TURNOVER RATE IN A RURAL SCHOOL DISTRICT IN SOUTHEASTERN NORTH CAROLINA - Monroe, Gregory E (East Carolina University, 2017)
The purpose of this study was to examine the variables that contributes to high teacher turnover rate in one Southeastern rural school district. The study used the Gap Analysis for Problem-solving, Planning, and School Improvement (GAPPSI) method approach to improve the current state of the problem by determining if there were common variables contributing to the high rate of teacher turnover. Participants responded to a survey based on a five-point scale with a mid-point or neutral selection choice. Furthermore, the study included interviews with participants who were currently employed or had been previous employed in the study school district. Two study questions guided this study. First, what factors contributed to teachers leaving the study school district, and the second, what factors contributed to teachers staying in the study school district? The findings of the data collected did not note any trends or a single variable that contributed to teachers' decisions to leave the study school district. However, having a more precise perspective and understanding of the problem will help the study school district in addressing its teacher retention efforts and decreasing its teacher turnover rate.
Keywords: school district; Teacher turnover--North Carolina; Rural schools--North Carolina; Employee retention--North Carolina